The effectiveness of the treatment of cows with mastitis - D. B. Zainettinova; N. N. Muhamadieva; M. N. Julanov; V. Yu. Stefanyk; V. V. Zaviruha; I. A. Sarhambaeva (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки, 2019)
The main sector of agriculture in Kazakhstan, including the East Kazakhstan region is cattle breeding and, in particular, cattle breeding, which is determined by climatic and geographical conditions. However, successful reproduction and increase in livestock productivity is largely hampered by infertility and mastitis, and as a result they cause significant economic damage and reduce the reproduction rate and profitability of dairy cattle. Recently, the number of subclinical mastitis in cows has increased, which subsequently lead to profound morphological and functional changes in the mammary gland, a decrease in milk productivity and quality. Mastitis can be caused by various reasons, primarily poor or inadequate feeding, poor care, improper maintenance and use of animals, negligent attitudes towards organizing and conducting artificial insemination, due to various diseases of the genital organs, which appear most often during childbirth and the postpartum period. The quality control of the milk of cows was investigated by California test and DEDM (Device for Express Diagnostic of Mastitis). The express methods that we used allowed us to identify the subclinical and clinical forms of mastitis and timely treat it. Laboratory studies on the presence of somatic cells in milk were also conducted. After the detection of breast diseases, complex symptomatic treatment was performed. For the treatment of various forms of mastitis, drugs were used: mastiet forte - intracisternally for five days at a dose of 10 ml 2 times a day for five days in a row. Mastiet Forte has a high therapeutic efficacy in subclinical and clinical forms of cow mastitis. And the drug ketoprof  has also been used. Ketoprof  as an anti-inflammatory agent was used intramuscularly – 3 ml per 100 kg of animal weight 1 time per day for 3 days in a row. Klineksin 5%, as an antibacterial agent, was used intramuscularly at a dose of 1 ml per 50 kg of body weight 1 time per day for 3 days in a row. Antimicrobial agents and biologically active substances needed to be combined for successful therapy. Such biologically active substances include vitamin of Helsivit. They were used subcutaneously – 6 ml once.